Virulent MDR Edwardsiella tarda from stinging catfish (Heteropneustes fossilis) - Mst. Tachhlima Aktar; Bushra Benta Rahman Prapti; Aminur Rahman; Mst. Ayesha Siddyqua; Muhammad Tofazzal Hossain; Mahbubul Pratik Siddique (PLoS ONE, 2026)
Edwardsiellosis, caused by Edwardsiella tarda , is a highly pathogenic disease affecting both freshwater and marine fish, leading to mass mortality. This study encompassed the molecular detection, virulence and antibiogram profiling of E. tarda from Heteropneustes fossilis (stinging catfish). A total of 40 fish samples were collected from different fish farms in the Mymensingh district. Isolation of E. tarda was performed using selective media, followed by identification through morphological, cultural, and biochemical testing, and confirmed through polymerase chain reaction (PCR). Antibiogram was performed following the disc diffusion method, and virulence and antibiotic resistance genes were detected through PCR. 19 out of 40 fishes were positive for Edwardsiella infection and 32 E. tarda were isolated. PCR assays consistently amplified gro EL (623 bp), gyr B (415 bp), etf A (415 bp), and etf D (445 bp) genes, respectively. The prevalence of virulence genes was: gad B (17%), muk F (35%), fim A (10%), and cit C (12.5%). The antibiogram revealed that the highest resistance (90.63%) was found against cotrimoxazole and amoxicillin, whereas sensitive (100%) to gentamicin and meropenem. Among 32 isolates, 90.75% were found to be multi-drug resistant (MDR). Again, multiple antibiotic resistance (MAR) index analysis revealed the highest value of 0.61, and 93.75% of isolates have an MAR index above 0.2. Resistance gene distribution was observed as the highest (62.5%) isolates harbored the tet A gene and the lowest (21.88%) isolates harbored qnr B. It could be concluded that MDR and pathogenic potential E. tarda was present in stinging catfish, posing a potential threat to animals, humans, and the environment.